Analysis of terminological literacy of dental lexicon - N. N. Fejzrahmanova; V. N. Trezubov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
The paper contains the quantitative analysis of contextual lexical literacy of 9 magazines and 3 illustrated newspapers (218 articles) on stomatology, 9 textbooks, 28 manuals for higher education institutions, 148 theses from the collections of scientific works. Besides, 126 headings of articles and 57 reports, lectures, seminars are analyzed. Calculations of relative and absolute measures were carried out by the formulas offered by authors of the work. Thus the rather high percent of the errors in written and oral speech of dentists was revealed in all tested editions. On the basis of the received results the authors drew the conclusion of the necessary inclusion of lexical and terminological courses in educational process and creation of active forms of standard highly specialized dictionaries which need to be used as manuals in training process.